Seren Taun Leuit Si Jimat: Tradition From Generations as a Form Of Gratitude of the Kasepuhan Ciptagelar Community for Agricultural Products - Desiany, Mia; Zahra, Trisha Fauziah; Alghifari, Gilang Arya; Iqbal, Muhamad (Jurnal Pendidikan Ilmu Sosial, 2022)
Indonesia as a multicultural country certainly has a variety of traditions that have grown in each region for generations, just as Kasepuhan Ciptagelar really upholds the traditions that have been passed down by the ancestors since the 600s last year in the form of the Seren Taun Leuit Si Jimat ritual. Seren Taun Leuit Si Jimat is used as a manifestation of the gratitude of the people of Kasepuhan Ciptagelar for the harvest. This research method uses qualitative methods with literature study data collection techniques to produce secondary data from various relevant sources. Based on the results of the study, it was found that Seren Taun Leuit Si Jimat is interpreted by handing over rice to traditional leaders to be stored in a rice barn as a manifestation of gratitude alone as well as a form of hope for the next harvest period. By storing rice in the granary, it can bring the Ciptagelar Kasepuhan to be stable in food. Therefore, Kasepuhan Ciptagelar highly respects rice because it realizes that the existence of rice is very important in life.